ChemInform Abstract: An Aluminum Dihydride Working as a Catalyst in Hydroboration and Dehydrocoupling. Issue 33 (July 2016) - Yang, Zhi; Zhong, Mingdong; Ma, Xiaoli; Nijesh, Karikkeeriyil; De, Susmita; Parameswaran, Pattiyil; Roesky, Herbert W.
Abstract: An aluminum dihydride complex catalyzes both the hydroboration of terminal alkynes and the dehydrocoupling of boranes with amines, thiols, and phenols, respectively, to form compounds with B—N, B—S, and B—O under elimination of H2 .